Methodical Conditions for the Implementation of Images of the Environment - Kosimova Gavhar Islomovna (Researchparks Publishing, 2022)
The article describes the process of forming primary school students' perceptions of the natural world: the system as a set of interconnected and interdependent systems. it is reported that these subdivisions combine to achieve educational goals and objectives.